The Role of Women in Education in Feminism Study - M. Saiful Bahri; Fahrurrozi Dahlan; Faizah Faizah; Moh. Fakhri; Nazar Ma'amy (Universitas Muhammadiyah Enrekang, 2022)
This research aims to find out the role of women in Education. This research uses a qualitative approach. This type of research uses a type of case study research. A case study is a study of